The quality factor for detecting node isolation attack in mobile ad hoc networks using OLSR protocol. Issue 4 (11th November 2021) - Nabou, Abdellah; Laanaoui, My Driss; Ouzzif, Mohammed
The Optimised Link State Routing (OLSR) protocol is a proactive routing protocol for Mobile Ad hoc Network (MANET), it is more suitable for large and dense mobile networks thanks to its new concept of Multi-Point Relay (MPR) nodes that reduce the overhead of the network, unfortunately the performance of OLSR routing protocol can be affected by various routing attacks. Node Isolation Attack is considered as a Denial of Service (DOS) attack that affects the function of OLSR routing protocols precisely by isolating the victim nodes and hiding them from the network. In this paper, we propose a new method to detect the Node Isolation Attack by using a modified version of the Quality Factor (Q) that is applied in the physical domain in order to calculate the Q of OLSR control messages and detect the attack. The experimental results show that when the attack is launched in the network between 30 second and 70 second, our method can detect it without any modification in the algorithm of OLSR protocol.